The Effect of Drill Bit Features on Surface Quality, Drill Wear and Drilling Cost-Sustainable Drilling - Kiyak, Murat (Jan Evangelista Purkyne Univ, 2026)
In drilling operations, hole quality is affected by factors such as drill diameter, drilling parameters, drill bit properties, workpiece material. A large portion of the drilling energy is converted into thermal energy, which can be measured as temperature. In this study, surface roughness of holes, drill tip wear and drill tip temperatures were determined using two different workpiece materials and three different drill tips. Furthermore, the costs of holes drilled with different drill bits were determined and interpreted based on drill bit characteristics. The results obtained can be optimized according to the process parameters and it has been shown that a more sustainable and much more economical manufacturing can be achieved by avoiding the use of additional reaming or internal grinding for the desired surface quality and eliminating negative environmental effects.
Keywords: Hole surface roughness; Drill bit temperature; Drill wear; Hole cost; HOLE QUALITY; TOOL WEAR; MACHINING PARAMETERS; TEMPERATURE; STEEL; OPTIMIZATION; ACCURACY; DIAMETER; FORCE; Engineering; Materials Science